Teacher’s strategies to enhance students’ speaking engagement in ESP classroom at vocational school - Putri, Nadela Devanika; Seinsiani, Izzati Gemi (Universitas Negeri Semarang, 2025)
Speaking proficiency plays a vital role in English language education, especially in vocational settings where learners are expected to use English in professional environments. While English for Specific Purposes (ESP) is gaining more recognition, there are still not enough studies exploring how focused teaching strategies influence student engagement in speaking tasks in vocational ESP contexts. This project investigates the teaching strategies used by an English teacher to promote student engagement in speaking, the challenges encountered during implementation, and the reported impacts of those strategies in an ESP setting for Mechatronics students in a vocational high school. A qualitative case study approach is used, with data collected through class observations, teacher interviews, and document analysis. Findings indicated that the teacher applied a series of speaking strategies and practice, such as project-based learning (PjBL), role-play, group discussions, and drilling practices, and these all responded to different dimensions of student participation; specifically, behavioral, emotional, and cognitive participation. Challenges included, distractions of mobile phones, poor instructional time and large class sizes, yet the methods seemed to foster students' participation. Learners with the highest levels of proficiency reported the highest levels of confidence; while learners that participated with lower levels of proficiency reported that they benefited from more direct guided instruction. The study suggests that the use of a range of speaking strategies in an ESP context can be effective in engaging and involving students in learning contexts. The implications of this study include the necessity of improving the practices of teachers, educational entities, and policymakers', providing vocational students for communication requirements in the workplace.